BEHAVIORAL FLEXIBILITY IN PREPARATION METHODISTS - ORGANIZERS OF THE SYSTEM PRESCHOOL EDUCATION - O.L. Marachkivska (Academy of Cognitive and Natural Sciences, 2007)
Іп given clause the essence of behavioral flexibility, as important characteristic of professionalism of the methodologist-organizer working in preschool establishment is opened. Aspects are staticized by professional methodical activity.